Evaluasi Penyetelan Relai Arus Lebih dan Relai Ganguan Tanah Pada Penyulang J.3 gardu Karang Joang Balikpapan - andi asni b; Muh Kayin Saleh; Bambang Sugeng (Jurnal Teknik Elektro Uniba (JTE UNIBA), 2017)
Abstract-Medium voltage network is one of the distribution ofelectricity from generators to the consumer. The voltage will beseparated to each feeder for its distribution. If the rate of consumerneeds is higher, PLN demanded to add new feeder. Electric powerdistribution requires reliability in maintaining the distributionequipment from fault, including short circuit. So, to minimize thefault, protection system that meets the requirements of sensitivity,reliability, selectivity and speed, which is all depends on theprecision in setting protection equipment One of the protectivedevices that used in medium voltage network is an over currentrelay (OCR) and ground fault relay(GFR). This research discussesevaluation between the OCR and GFR setting, at the J.3 in KarangJoang substation. The comparisonresult between calculation andattached data in Karang Joang substation almost same. Thecalculation from OCR setting in incoming side acquired TMS =0,1955. Meanwhile the OCR setting in outgoing side acquired TMS=0,1294. GFR setting in incoming side acquired TMS 0,2807.Meanwhile GFR setting in outgoing side acquired TMS = 0,1102.This result showed that attached setting in Karang Joang Substationstill considered in good condition.